Revitalisasi Ilmu Dakwah: Kajian Mabadi ‘Asrah Ilmu Dakwah - Tata Sukayat (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2012)
Although dakwah activities have been crossed such a long history, but dakwah as a science is still relatively new. Moreover, the study area is almost tangent to the dakwah as a science with some other existing knowledge and have been developed more earlier, dakwah science have been so important for us to develop in more powerful, which in turn can generate a deeper motivation to develop it. Despite much research on the revitalization of the science mission with a diverse range of perspectives, but this paper will look at the process of revitalizing the science of dakwah in perspective mabadi 'asrah which has been well-known in the Islamic sciences tradition that are expected to be more independent as well as seeking the position and its relationship with other sciences which has been exist before.